2021
DOI: 10.1017/s0022029921000625
|View full text |Cite
|
Sign up to set email alerts
|

Fermented foods and probiotics: An approach to lactose intolerance

Abstract: The aim of this review was to present various topics related to lactose intolerance with special attention given to the role of fermented foods and probiotics in alleviating gastrointestinal symptoms. Lactose intolerance is a common digestive problem in which the human body is unable to digest lactose, known as milk sugar. Lactose intolerance can either be hereditary or a consequence of intestinal diseases. Recent work has demonstrated that fermented dairy products and probiotics can modify the metabolic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 78 publications
(152 reference statements)
0
28
0
Order By: Relevance
“…Therefore, today it is urgent to develop scientific approaches to the creation of functional products that, by their composition and effect on the body of an aging person, should have a significant biological effect -provide nutrients and perform a preventive function [16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, today it is urgent to develop scientific approaches to the creation of functional products that, by their composition and effect on the body of an aging person, should have a significant biological effect -provide nutrients and perform a preventive function [16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…Fermented milk drinks have been developed using a bacterial culture that normalizes the composition of the beneficial intestinal microflora. They contain vitamins and mineral elements, as well as animal fat replaced with vegetable [19,28].…”
Section: Recommendedmentioning
confidence: 99%
“…Organic acid produced by probiotics strain contribute to gut health benefits [22]. Probiotic bacteria contain B-galactosidase to improve lactose maldigestion [23]. Bacteria in gastrointestinal serve a barrier system for against pathogens.…”
Section: 70±027amentioning
confidence: 99%
“…This not only results in the production of lactic acid upon utilization of lactose but also makes the product more nutritious and digestible. Putative health benefits of probiotics have been proposed (see review by Ibrahim et al ., 2021) and in addition the dairy product market has also witnessed development of products with a combination of probiotics and prebiotics, also known as ‘synbiotic’ dairy products (Chand et al ., 2021; Zahed et al ., 2021).…”
mentioning
confidence: 99%
“…Fermented milk beverages are universally accepted and enjoyed, and can be given added functionality by the incorporation of probiotics, prebiotics and other health promoting ingredients from herbal and plant sources (Sharma et al ., 2021a). It is suggested that beverages of this sort could help in combating various intestinal disorders as well as hypertension problems, and consumption may be correlated to improved digestion, lactose utilization and prevention of colon cancer (Sarwar et al ., 2019; Ibrahim et al ., 2021). However, the main problem associated with probiotic/prebiotic incorporated product is the viability of micro-organisms in the product by the end of the storage period.…”
mentioning
confidence: 99%